Sustainable infrastructure : the guide to green engineering and design - Sarte, S. Bry, 1972- (Hoboken, N.J. : John Wiley & Sons, 2010)
'As more factors, perspectives, and metrics are incorporated into the planning and building process, the roles of engineers and designers are increasingly being fused together. The Art of Eco-Engineering explores this tend with in-depth look at sustainable engineering practices in an urban design as it involves watershed master-planning, green building, optimizing water reuse, reclaiming urban spaces, green streets initiatives, and sustainable master-planning. This complete guide provides guidance on the role creative thinking and collaborative team-building play in meeting solutions needed to affect a sustainable transformation of the built environment'--
'In-depth look at sustainable engineering practices in an urban design context, this book offers guidance on developing strategies for implementing the complex solutions needed to affect a sustainable transformation of the built environment. With coverage of watershed master-planning, green building, optimizing water reuse, reclaiming urban spaces, green streets initiatives, and sustainable master-planning, the book supplements the core reference material with international examples and case studies'--
Includes bibliographical references and index.
Keywords: Sustainable engineering; Sustainable design